Tricho-cutaneous hypomelanic nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
A tuft of hair lighter than the remaining hair is found in some hereditary diseases as piebaldism and Waardenburg syndrome and in acquired diseases such as segmental and perinevic vitiligo and alopecia areata in the regrowth phase of adults; in all these conditions the hair is white and so different from our case. A nevoid area of lighter hair but not white was described exceptionally in case of very extensive hypomelanic nevi involving also the skin (1, 3); also cases of nevoid heterochromia involving only the scalp were reported (2, 3). Finally a heterochromia of the hair was also described in the case of iron deficiency anemia. Our case is unique because it is characterized by a non systematized hypomelanic nevus, with modest size, of the forehead skin on which a tuft of lighter hair stands.